2014
DOI: 10.1089/cell.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cells from Hair Follicle Bulge Neural Crest Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) are promising candidates for the study of disease models as well as for tissue engineering purposes. Part of a strategy to develop safe reprogramming technique is reducing the number of exogenous reprogramming factors. Some cells types are more prone to reprogramming than others. iPSC induction with less reprogramming factors has been described in cells with endogenous expression levels of pluripotency genes, such as neural stem cells. Because multipotent neural crest ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Research has found that the HFSc have multidirectional differentiation potential, which can differentiate into skin, hair follicles, sebaceous glands and participates in skin wound healing process (10). Previous study has showed that generation of induced pluripotent stem cells can be differentiated from hair follicle bulge neural crest stem cells (11). Lien et al have indicated that in vivo transcriptional governance of HFSc can be regulated by Wnt regulators (12).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that the HFSc have multidirectional differentiation potential, which can differentiate into skin, hair follicles, sebaceous glands and participates in skin wound healing process (10). Previous study has showed that generation of induced pluripotent stem cells can be differentiated from hair follicle bulge neural crest stem cells (11). Lien et al have indicated that in vivo transcriptional governance of HFSc can be regulated by Wnt regulators (12).…”
Section: Introductionmentioning
confidence: 99%